2020
DOI: 10.3892/ol.2020.11865
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase IV inhibits cell proliferation in gastric cancer by regulating the cell cycle

Abstract: Carbonic anhydrase IV (CA4) is silenced in colorectal cancer. However, the effect of CA4 on the development of gastric cancer (GC) is poorly understood. The present study aimed to determine the role of CA4 in GC tumorigenesis and its underlying molecular mechanism. The levels of CA4 in GC cells and tissues were evaluated by reverse transcription-quantitative PCR and immunohistochemistry. CA4 expression was suppressed in GC cells and tissues compared with adjacent healthy tissues and normal human gastric epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…15 The role of CA4 in gastric cancer (GC) tumorigenesis was investigated in this study by evaluating the levels of CA4 in GC cells and tissues and conducting analyses to determine its impact on GC cell lines. 16 The results demonstrate that CA4 may serve as a diagnostic biomarker and potential therapeutic target in GC by inhibiting cellular proliferation via regulating the expression of cell cycle-associated proteins. The MT1F gene is a member of the metallothionein (MT) gene family.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…15 The role of CA4 in gastric cancer (GC) tumorigenesis was investigated in this study by evaluating the levels of CA4 in GC cells and tissues and conducting analyses to determine its impact on GC cell lines. 16 The results demonstrate that CA4 may serve as a diagnostic biomarker and potential therapeutic target in GC by inhibiting cellular proliferation via regulating the expression of cell cycle-associated proteins. The MT1F gene is a member of the metallothionein (MT) gene family.…”
Section: Discussionmentioning
confidence: 90%
“…While the previous research has examined the role of CA4 in physiological processes such as acid–base balance and respiration, 14 recent studies have also suggested that CA4 may play a role in cancer development and progression 15 . The role of CA4 in gastric cancer (GC) tumorigenesis was investigated in this study by evaluating the levels of CA4 in GC cells and tissues and conducting analyses to determine its impact on GC cell lines 16 . The results demonstrate that CA4 may serve as a diagnostic biomarker and potential therapeutic target in GC by inhibiting cellular proliferation via regulating the expression of cell cycle‐associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that NEK2, TOP2A, PLK1, CA4, CDK5R1, AURKB, and F2 have important regulatory roles in cell cycle, DNA replication, homologous recombination, and others (Chabalier-Taste et al, 2016;Fan et al, 2019;Zeng et al, 2019;Wang et al, 2020;Ha et al, 2022). The expression level of NEK2 in human gastric cancer (GC) tissues is significantly upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the tumour tissues and normal adjacent mucosal tissues was 5 cm. The inclusion and exclusion criteria for the patients were based on the method of Wang B et al [ 20 ].…”
Section: Methodsmentioning
confidence: 99%